Drought and presence of ants can influence hemiptera in tropical leaf litter. (17th March 2020) - Goldman, Anna E.; Bonebrake, Timothy C.; Tsang, Toby P. N.; Evans, Theodore A.; Gibson, Luke; Eggleton, Paul; Griffiths, Hannah M.; Parr, Catherine L.; Ashton, Louise A.
Abstract: Climate change is predicted to impact tropical rain forests, with droughts becoming more frequent and more severe in some regions. We currently have a poor understanding of how increased drought will change the functioning of tropical rain forest. In particular, tropical rain forest invertebrates, which are numerous and biologically important, may respond to drought in different ways across trophic levels. Ants are a diverse group that carry out important ecosystem processes, shaping ecosystem structure and function through predation and competition, which can influence multiple trophic levels. Hemiptera are a mega‐diverse order, abundant in tropical rain forests and are ecologically important. To understand the roles of ants in exerting predation and competition pressure on invertebrates in tropical rain forests during drought and a post‐drought period, we established a large‐scale ecosystem manipulation experiment in Maliau Basin Conservation Area in Malaysian Borneo, suppressing the activity of ants on four 0.25 ha plots over a two‐year period. We sampled hemipterans found in the leaf litter during a drought (July 2015) and a post‐drought period (September 2016) period. We found significant shifts in the assemblage of hemipterans sampled from the leaf litter following ant suppression. Specifically, for ant‐suppression plots, the species richness and abundance of herbivorous hemipterans increased only during the post‐drought period. For predatory hemipterans, abundance increased with ant‐suppression regardless of drought conditions, and we found marginal evidence for a species richness increase during the post‐drought period with little or no change in the drought period. These results illustrate how ants in tropical forests structure invertebrate communities and how these effects may vary with climatic variation. Abstract in Malay is available with online material. Abstrak: Perubahan iklim diramalkan akan memberi kesan terhadap hutan hujan tropika, dengan kemarau menjadi lebih kerap dan lebih teruk di sesetengah kawasan. Pada masa ini, kita mempunyai pemahaman yang kurang baik tentang bagaimana peningkatan kemarau akan mengubah fungsi hutan hujan tropika. Invertebrata hutan hujan tropika khususnya, adalah banyak dan penting secara biologi, dan boleh bertindak balas terhadap kemarau dalam pelbagai cara pada peringkat trofik. Semut adalah kumpulan pelbagai yang menjalankan proses ekosistem yang penting, iaitu membentuk struktur ekosistem dan berfungsi melalui predasi dan persaingan, yang mempengaruhi lapisan trofik yang banyak. Hemiptera adalah order yang sangat pelbagai, banyak di hutan hujan tropika dan sangat penting secara ekologi. Bagi memahami peranan semut dalam mengetengahkan tekanan predasi dan persaingan terhadap invertebrata di hutan hujan tropika semasa dan selepas musim kemarau, kami telah menjalankan eksperimen manipulasi ekosistem berskala besar di Kawasan Konservasi Lembangan Maliau, dalam wilayah Malaysia di Kepulauan Borneo dengan menindas aktiviti semut pada empat plot 0.25 ha sepanjang tempoh dua tahun. Kami mengumpul sampel hemipteran yang terdapat dalam serasah daun semasa musim kemarau (Julai 2015) dan selepas musim kemarau (September 2016). Kami mendapati peralihan yang signifikan dalam kumpulan hemipteran yang diambil dari serasah daun selepas penindasan semut. Khusus untuk plot penindasan semut, kekayaan spesies dan kelimpahan hemipteran herbivora meningkat hanya selepas musim kemarau. Kelimpahan bagi hemipteran pemangsa meningkat dengan penindasan semut tanpa mengira keadaan kemarau, dan kami mendapati bahawa berlaku peningkatan kekayaan spesies selepas kemarau dengan sedikit atau tiada perubahan dalam tempoh kemarau. Hasil ini menggambarkan bagaimana semut menstruktur komuniti invertebrata di hutan tropika dan bagaimana kesan ini mungkin berbeza dengan variasi iklim yang lain.